2016
DOI: 10.1007/s11069-016-2181-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa

Abstract: To analyse inner-and inter-annual changes, disaster events of 55 countries in Africa from 1990 to 2014 recorded in the International Disaster Database (EM-DAT) were recounted by year and month and were reorganised in five different regions. Thematic maps of flood disasters in Africa between 1990 and 2014 were drawn using ArcGIS 9.3 to research the spatial distribution patterns of average annual flood frequency, total deaths, total affected, and damage. There were eight natural and socio-economic indicators cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 11 publications
4
42
0
Order By: Relevance
“…Kenya tends to experience increased rainfall during the rainy seasons and is prone to flooding during El Niño episodes. Heavy rainfall events caused landslides in 1997-1998 in several areas of Kenya Ngecu and Mathu (1999), Li et al (2016), Mutemi (2003), Muthama et al (2014) Coastal ecosystems…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Kenya tends to experience increased rainfall during the rainy seasons and is prone to flooding during El Niño episodes. Heavy rainfall events caused landslides in 1997-1998 in several areas of Kenya Ngecu and Mathu (1999), Li et al (2016), Mutemi (2003), Muthama et al (2014) Coastal ecosystems…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The economy of the region is heavily dependent on rainfall. The region is one of the most drought and flood-prone areas in Africa (Li et al 2016), where extreme events have been causing devastating effects on the populations of the region. Local factors such as complex terrain, large inland water bodies (Lake Victoria) and land heterogeneity (with the highest peak of Africa, mount Kilimanjaro) and their consequent interactions with large-scale climate forcing mechanisms, contribute to the diverse spatial rainfall patterns over the region.…”
Section: Overview Of Study Areamentioning
confidence: 99%
“…Global meta‐analysis of the relationship between forest cover and flooding by Bradshaw et al () and Van Dijk et al () does not conclusively identify forest cover as a significant predictor of hydrologic extremes, with most flooding reports explained well solely by population density. In a series of regional studies, Li et al (), Bhattacharjee and Behera (), Brookhuis and Hein (), and Tan‐soo et al () present evidence in the form of meta‐analyses of land cover and flooding records that deforestation results in an increased frequency of socioeconomic flood loss in Africa, India, Trinidad, and Malaysia, respectively. In a similar study, Brogna et al () demonstrated only a slight influence of forest cover on flood frequency in Belgium.…”
Section: Introductionmentioning
confidence: 99%